التّماهي بين السّير الذّاتي والتّخييلي في التّجربة الرّوائيّة لزهور ونيسي - حدّة بولعراس (My University, 2023)
Abstract The study, titled “The Identification between Autobiography and Fiction in the Novel Experience of Zahour and Nissi,” aims to study the interplay between the autobiographical and fictional elements in the fictional works of the writer Zahour and Nissi. We chose the novel “Free School Diaries” as a subject for research, in which we tried to reveal the mixing and interaction between the two elements. In it, and how does this overlap enhance the interaction of the recipient with the events of the novel Accordingly, the study was classified as follows: an introduction, two chapters, and a conclusion. The first chapter dealt with autobiography and imagination, concepts and upbringing. It was a theoretical chapter in which we presented the concepts, while the second chapter was an applied study in which we tried to study the interaction between The autobiography and the imaginary in the novel “Free School Diaries.” We concluded the work with a conclusion in which we summarized the results reached from this research, a list of sources and references that flowed into the course of the research, and a summary of the topics we touched upon ------------------ ملخّص: تهدف الدّراسة الموسومة ب" التّماهي بين السّير الذّاتي والتّخييلي في التّجربة الرّوائية لزهور ونيسي" إلى دراسة التّداخل بين عنصري السّير الذّاتي والتّخييلي في الأعمال الرّوائيّة للأديبة زهور ونيسي، وقد اخترنا رواية " يوميات مدرسة حرة" كمدونة للبحث، فحاولنا فيها الكشف عن التّمازج والتّفاعل بين العنصرين فيها، وكيف يعزّز هذا التّداخل تفاعل المتلقّي مع أحداث الرّواية، وعليه جاءت الدّراسة مبوّبةً كالآتي: مقدّمة وفصلين وخاتمة، فتناول الفصل الأوّل السّير الذّاتي والتّخييل المفاهيم والنّشأة، فكان فصلًا نظريًّا قدّمنا فيها المفاهيم، في حين أنّ الفصل الثّاني ورد تطبيقيًّا حاولنا فيه دراسة التّداخل بين السّير الذّاتي والتّخييلي في رواية "يوميات مدرسة حرة "، وذيّلنا العمل بخاتمة أوجزنا فيها النّتائج المتوصّل إليها من هذا البحث وقائمة المصادر والمراجع الّتي تصبّ في مجرى البحث، وفهرس للموضوعات الّتي تطرّقنا لها. ------------------ Résumé L'étude intitulée « Identité entre biographie autobiographique et biographie fictionnelle dans l'expérience narrative de Zuhur et Nissi » vise à étudier le chevauchement entre les éléments autobiographiques et fictionnels dans les œuvres romanesques de l'écrivain Zuhur Wanisi. du destinataire avec les événements du roman, et en conséquence l'étude a été classée comme suit : une introduction, deux chapitres et une conclusion. La biographie autobiographique et imaginaire du roman "Journal d'une école libre", et nous avons annexé l'ouvrage avec une conclusion dans laquelle nous résumons les résultats obtenus à partir de cette recherche et la liste des sources et références qui affluent au cours de la recherche, et un chevalier des sujets que nous avons abordés.
Keywords: autobiography; imagination; Zehour Onesie; novel.; السير الذاتي، التخييل، زهور ونيسي، الرواية; autobiographie; imaginaire; roman